Pengembangan Aplikasi Rekomendasi Kuliner di Kota Malang berbasis Mood pada Platform Android - Asti Dhiya Anzaria; Herman Tolle; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The habit of people eating outside the home makes the culinary business develop rapidly. Various eating places are spreading everywhere with a variety of unique and modern menus. In Malang, various types of food stalls such as crushed-chicken and coffee shops are scattered around the campus. This makes people confused looking for places to eat because there are so many dining options. Emotional conditions are known to affect food choices. Positive moods and negative moods lead one to different food preferences. Based on the existing problem, a solution is provided, a mood-based culinary recommendation system in Android platform using a certainty factor algorithm to process suitable recommendation data. User can take selfie to recognize their emotion which will be processed into suitable culinary recommendation. Based on the result of validation testing using the black box testing method gave a grade of 100% where all functions run as expected. The usability test result was 83 and the rating was excellent and the accuracy test result was 79.4%.